Early Effects of Long-Term Neurotoxic Lead Exposure in Copper Works Employees - Irina Böckelmann; Eberhard Pfister; Sabine Darius (Journal of Toxicology)
The situation of exposure in a copper works facility in Germany enabled early lead-induced neurotoxic effects to be investigated in the workers. The aim of the investigation was to study the long-term effects of small doses of lead on psychometric/psychophysiological performance of workers. The study involved 70 male lead exposed workers and 27 male controls with no neurotoxic exposure. All test persons were subjected to the method of investigation involving performance data, physiological strain data, and the subjective state. It was found that of the psychometric performance parameters, only the mainly motor performance parameters had a potential for being neurotoxic early indicators. Preferably centrally influenced performance parameters were found to be less suitable early indicators. The lead-exposed subjects exhibited a slowed poststrain resetting behaviour of the vegetative nervous system, which correlated with the individual blood lead level. This was attributed to vagus depression, which had already started in the prevailing situation of exposure and was reflected by diminished cardiac phase duration variability. Our results indicate that it is necessary to more critically choose the lead level standards in the air on the working area. Heart rate variability may be affected even at small lead concentration.